Swot Analysis Of Tahu Tempe In Efforts To Develop The Food Industry In South Bengkulu District - Rahmadannia, Shofi; Indriasari, Nia; Hardinata, Dodi (Jurnal Pusat Manajemen, 2024)
This research presents a SWOT analysis of efforts to develop the tofu and tempeh food industry in South Bengkulu Regency. This research aims to analyze the strengths, weaknesses, opportunities and threats (SWOT) in the development of the tofu and tempeh industry in South Bengkulu Regency. The method used is qualitative descriptive analysis with a SWOT approach. Data was obtained through interviews with tofu and tempeh producers and field observations. This research concludes that to develop the tofu and tempe industry in South Bengkulu Regency, a strategy is needed that includes increasing market expansion and strengthening the managerial capabilities of producers. In this way, the tofu and tempeh industry can become a more competitive sector and contribute significantly to the local economy.